The Marine Strategy Framework Directive and the ecosystem-based approach – pitfalls and solutions. Issue 1 (15th July 2015) - Berg, Torsten; Fürhaupter, Karin; Teixeira, Heliana; Uusitalo, Laura; Zampoukas, Nikolaos
Highlights: Use of the species level criteria within descriptor 1 for mobile species only. Use of the habitat level criteria within descriptor 1 for immobile components only. Expand descriptor 4 with the functional interactions between trophic entities. Redefine descriptor 6 as pressure or state descriptor only, avoid mixing. Include indicators on ecosystem functioning and services across descriptors. Abstract: The European Marine Strategy Framework Directive aims at good environmental status (GES) in marine waters, following an ecosystem-based approach, focused on 11 descriptors related to ecosystem features, human drivers and pressures. Furthermore, 29 subordinate criteria and 56 attributes are detailed in an EU Commission Decision. The analysis of the Decision and the associated operational indicators revealed ambiguity in the use of terms, such as indicator, impact and habitat and considerable overlap of indicators assigned to various descriptors and criteria. We suggest re-arrangement and elimination of redundant criteria and attributes avoiding double counting in the subsequent indicator synthesis, a clear distinction between pressure and state descriptors and addition of criteria on ecosystem services and functioning. Moreover, we suggest the precautionary principle should be followed for the management of pressures and an evidence-based approach for monitoring state as well as reaching and maintaining GES.